Perancangan Sistem Suspensi Dan Analisis Pegas Sepeda Motor Listrik Phb Menggunakan Finite Elemen Metode (FEM) - Budi, Sigit Setijo; Sanjaya, Firman Lukman; Ayu, Fitri (Fakultas Teknik UMSU, 2022)
Currently, motorcycles in general and especially electric motorcycles, are equipped with various technologies, one of which is a suspension system. Electric motorcycle suspension has advantages, one of which is the damping of the rear suspension and has a suspension that is comfortable for daily mobility and tends to be soft when passing through damaged roads. The purpose of this study was to determine the load of the suspension using the finite element method. In this study, the springs received loads of 60kg, 80kg, 100kg and 120kg. From the results of this study, ST 37 suspension has better performance compared to AISI 1020.